Extraction and Evaluation: The Viability of the Three Varieties of Banana (Musa Paradisiaca) Exocarps as Potential Sources of Acetic Acid (American Journal of Life Science and Innovation, 2022)
The banana (Musa paradisiaca) exocarps have been a substantial source for maintaining human health and are the fast-growing herbaceous perennials arising from underground rhizomes. The ripe banana is useful in acidity. This study aimed to evaluate how the banana exocarps from ripe ones, can be made into vinegar. Also, to properly analyze the physicochemical properties (pH and color) and to determine the acetic acid content of the three selected varieties of banana exocarps if it conforms to the set standards. The most accessible in producing acidity is the Latundan (Musa acuminata musa balbisiana AAB Group), but all of the samples are accessible in producing acidity. In pH determination the highest in acidity is Lacatan (Musa acuminata C.) pH 4, while the Cardaba (Musa acuminata balbisiana ABB Group), is pH 3.5, and the lowest is the Latundan pH 3. All of the samples do not have pleasant odor, furthermore the samples well tested and undergo many stages of pasteurization. Thus, the study encourages further development of some spices and food additives and by application of new principles discovered, aside from extending the fermentation time.